What determines Saudi Arabia's development finance? An empirical approach - Elham Bokhari; Jinhwan Oh (Global Business & Finance Review (GBFR), 2022)
Purpose: This paper empirically examines determinants of Saudi Arabia's development finance allocation and seeks implications. Design/methodology/approach: Based on the OLS and Tobit estimation, this paper analyzes a dataset covering Saudi Arabia's 111 bilateral aid recipient countries during the time period 2015 to 2020. Findings: This paper finds that Saudi's aid allocation considers both donors' interest (DI) and recipients' needs (RN) given that less populous and relatively lower income developing countries, with strong commercial ties with the Kingdom tend to receive more aid from Saudi Arabia. This result is robust across all the analyses, supported by statistical significance. Research limitations/implications: Geopolitical factors also matter considering that Arab countries are, on average, receive more aid from the Kingdom while other countries do not, and this confirms Arab solidarity. The Kingdom places a high importance on their non-interference policy in nation states' sovereignty and their territorial integrity. The Kingdom has a short history as an aid donor. As such, bilateral data is available only since 2015, which is a major caveat in this study. Originality/value: Existing literature mostly deals with OECD DAC countries in examining aid determinants. This is one of the first studies in this field of literature empirically examining Saudi Aid. This study is expected to shed light to other emerging donors and promote effective South-South cooperation.
Keywords: 650; Development Finance; Saudi Arabia; DI-RN; Geopolitics; Panel Data